Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a) Thay f(0);f(\(-\frac{1}{2}\)) vào f(x)=2-x2 ta được:
\(f\left(0\right)=2-0^2=2\)
\(f\left(-\frac{1}{2}\right)=2-\left(-\frac{1}{2}\right)^2=\frac{7}{4}\)
b) y = f(x) = 2-x2
Ta có f(x-1) = 2- (x-1)2
f(1-x) = 2 - (1-x)2 = 2 - (x-1)2
nên f(x-1) = f(1-x)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)Với x1 = x2 = 1
\( \implies\) \(f\left(1\right)=f\left(1.1\right)\)
\( \implies\) \(f\left(1\right)=f\left(1\right).f\left(1\right)\)
\( \implies\)\(f\left(1\right).f\left(1\right)-f\left(1\right)=0\)
\( \implies\) \(f\left(1\right).\left[f\left(1\right)-1\right]=0\)
\( \implies\) \(\orbr{\begin{cases}f\left(1\right)=0\\f\left(1\right)-1=0\end{cases}}\)
Mà \(f\left(x\right)\) khác \(0\) ( với mọi \(x\) \(\in\) \(R\) ; \(x\) khác \(0\) )
\( \implies\) \(f\left(1\right)\) khác \(0\)
\( \implies\) \(f\left(1\right)-1=0\)
\( \implies\) \(f\left(1\right)=1\)
b)Ta có : \(f\left(\frac{1}{x}\right).f\left(x\right)=f\left(\frac{1}{x}.x\right)\)
\( \implies\) \(f\left(\frac{1}{x}\right).f\left(x\right)=f\left(1\right)=1\)
\( \implies\) \(f\left(\frac{1}{x}\right).f\left(x\right)=1\)
\( \implies\) \(f\left(\frac{1}{x}\right)=\frac{1}{f\left(x\right)}\)
\( \implies\) \(f\left(x^{-1}\right)=\left[f\left(x\right)\right]^{-1}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
\(a)f\left(x\right)=10x\)
\(\Leftrightarrow f\left(0\right)=10.0=0\)
\(\Leftrightarrow f\left(-1\right)=10\left(-1\right)=-10\)
\(\Leftrightarrow f\left(\frac{1}{2}\right)=\frac{10}{2}=5\)
\(b)\)Vì \(f\left(x\right)=10x\)
Nên: \(f\left(a+b\right)=10\left(a+b\right)\)
Và: \(f\left(a\right)+f\left(b\right)=10a+10b=10\left(a+b\right)\)
Do đó:
\(f\left(a+b\right)=f\left(a\right)+f\left(b\right)\left(đpcm\right)\)
\(c)\)Vì \(\hept{\begin{cases}f\left(x\right)=10x\\f\left(x\right)=x^2\end{cases}\Leftrightarrow x^2=10x}\)
\(\Leftrightarrow x^2-10x=0\)
\(\Leftrightarrow x\left(x-10\right)=0\)
\(\Leftrightarrow\hept{\begin{cases}x=0\\x-10=0\end{cases}\Leftrightarrow\hept{\begin{cases}x=0\\x=10\end{cases}}}\)
Vậy với \(\hept{\begin{cases}x=0\\x=10\end{cases}}\)thì \(f\left(x\right)=x^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có: y=f(x)=x2−2y=f(x)=x2−2
Thay f(2); f(1); f(0); f(-1); f(-2) vào hàm số:
f(2)=22−2=4−2=2f(2)=22−2=4−2=2
f(1)=12−2=1−2=−1f(1)=12−2=1−2=−1
f(0)=02−2=−2f(0)=02−2=−2
f(−1)=(−1)2−2=1−2=−1f(−1)=(−1)2−2=1−2=−1
f(−2)=(−2)2−2=4−2=2
a: f(0)=2
f(-1/2)=2-1/4=7/4
b: \(f\left(x-1\right)=2-\left(x-1\right)^2=2-\left(1-x\right)^2=f\left(1-x\right)\)